Tinjauan Literatur Theory of Planned Behavior (TPB) dengan Perilaku Safety Riding pada Remaja - Diandra Nova Alia; Luqman Effendi (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
Traffic discipline is the compliance of individuals or groups with applicable rules, orders, and prohibitions independenly without waiting for orders. Teenagers are still in an immature stage of development, easily influenced by emotions, want to look attractive, and often ignore traffic regulations. Unsafe driving is a major factor causing accidents among teenagers. This study aims to conduct a literature analysis on the relationship betweet element of the Theory of Planned Behavior (TPB) and safe driving behavior among teenagers. The research method used a literature review of scientific articles from 2017-2025 that focused on teenagers in Indonesia. Thhe research conducted a search and selection of literature using databases such as Google Scholar, PubMed. ProQuest, and Oneseacrh.id that have been published. The results of the study confirm that perceptions, subjective norms, and behavioral control have a significant impact than knowledge factors, but behavioral control is considered the most dominant factor. However, without strong self-efficacy, positive attitudes do not always translate into action. The conclusion of this study is that to foster safe driving behavior, youth safety interventions must focus on providing social support and increasing self-control.